Adipose Tissue Metabolic Function and Dysfunction: Impact of Burn Injury - Kaur, Supreet; Auger, Christopher; Jeschke, Marc G. (Frontiers in Cell and Developmental Biology, 2020)
For decades, adipose tissue had been considered as merely a storage depot and cushion to protect organs against trauma and injury. However, in recent years, a number of impactful studies have pinpointed the adipose tissue as an endocrine organ mediating systemic dysfunction in not only metabolic disorders such as obesity, but also in the stages following traumatic events such as severe burns. For instance, thermal injury induces a chronic β-adrenergic response associated with drastic increases in adipose lipolysis, macrophage infiltration, and IL-6 mediated browning of white adipose tissue (WAT). The downstream consequences of these physiological changes to adipose, such as hepatomegaly and muscle wasting, are only now coming to light and suggest that WAT is both a culprit in and initiator of metabolic disorders after burn injury. To that effect, the aim of this review is to chronicle and critically analyze the scientific advances made in the study of adipose tissue with regards to its role in orchestrating the hypermetabolic response and detrimental effects of burn injury. The topics covered include the magnitude of the lipolytic response following thermal trauma and how WAT browning and inflammation perpetuate this cycle as well as how WAT physiology impacts insulin resistance and hyperglycemia post-burn. To conclude, we discuss how these findings can be translated from bench to bedside in the form of therapeutic interventions that target physiological changes to WAT in order to restore systemic homeostasis following a severe burn.